APPLICATION OF ETHNO-PRAGMATIC LEARNING STRATEGIES IN INDONESIAN LANGUAGE LESSONS IN HIGH SCHOOL IN THE MERDEKA CURRICULUM (PENERAPAN STRATEGI PEMBELAJARAN ETHNO-PRAGMATIK PADA PELAJARAN BAHASA INDONESIA DI SMA PADA KURIKULUM MERDEKA) - Dewa Ayu Widiasri; I Wayan Gunartha; Nidya Fitri (Universitas PGRI Sumatera Barat, 2023)
The problems discussed in this study are adapting curriculum changes from the 2013 curriculum to the independent curriculum in Indonesian learning in high school. This curriculum is because not all teachers understand the application of the independent curriculum to learning, especially Indonesian learning. For this reason, ethno-pragmatic learning strategies are needed to integrate with the independent curriculum in high school. This ethno-pragmatic learning strategy can accommodate the achievements of the Indonesian learning curriculum in high schools so that character strengthening can be achieved by the independent curriculum policy set in Decree of the Head of Balitbang of the Ministry of Education and Culture, Research and Technology No. 028/H/KU/2021 concerning the learning outcomes of PAUD, SD, SMP, SMA, SDLB, SMPLB, and SMALB in the Driving School Program. The method is carried out with descriptive qualitative to understand students applying the Indonesian language curriculum in high school. Data were collected using observation methods, in-depth interviews, documentation with note-taking techniques, practical matching techniques, and focus group discussions with stakeholders in high school. The results showed that (1) the application of the ethno-pramatics method to Indonesian subjects in high school was able to accommodate the achievement of curriculum objectives in the use of the Indonesian language in a polite manner, and (2) The application of ethno-pragmatics methods to Indonesian subjects in high school can understand various multimodal texts based on context.